2020
DOI: 10.1038/s41598-020-64172-4
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Leptospira and their animal reservoirs: testing host specificity through experimental infection

Abstract: Leptospirosis is caused by pathogenic Leptospira transmitted through contact with contaminated environments. Most mammalian species are infectable by Leptospira but only few act as efficient reservoir being capable of establishing long term kidney colonization and shedding Leptospira in urine. In Madagascar, a large diversity of pathogenic Leptospira display a tight specificity towards their endemic volant or terrestrial mammalian hosts. The basis of this specificity is unknown: it may indicate some geneticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…Consistent with this, Theuerkauf et al (2013) found that Leptospira infection in several rodent hosts increased following the introduction of non-native black rats (Rattus rattus) to a Polynesian island, suggesting that a rise in rodent diversity amplified host infection. Evidence of host specificity and multiple Leptospira species within individuals suggests that this might be a result of cross-infection among co-occurring host species (Cordonin et al, 2019(Cordonin et al, , 2020Moseley et al, 2018). Other work suggests, however, that host diversity reduces infection prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this, Theuerkauf et al (2013) found that Leptospira infection in several rodent hosts increased following the introduction of non-native black rats (Rattus rattus) to a Polynesian island, suggesting that a rise in rodent diversity amplified host infection. Evidence of host specificity and multiple Leptospira species within individuals suggests that this might be a result of cross-infection among co-occurring host species (Cordonin et al, 2019(Cordonin et al, , 2020Moseley et al, 2018). Other work suggests, however, that host diversity reduces infection prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…1 week). Experimental work has demonstrated successful Leptospira infection 7 days post-infection [32,33], yet further work is needed to examine Leptospira spp. infection dynamics at a shorter timescale and determine how long rats can survive following AR exposure.…”
Section: Resultsmentioning
confidence: 99%
“…This absence of colonization might be related to a low infecting dose and/or from an infecting bacterial genomospecies that is unable to establish persistent renal colonization in a specific vertebrate species. This assumption is based on the existence of host- Leptospira molecular determinants required for renal colonization, an hypothesis substantiated by experimental infections in which bat-borne and Tenrec-borne Leptospira were not able to lead to chronic infection in rats (Cordonin et al . 2020).…”
Section: Discussionmentioning
confidence: 99%